Association of Hearing Impairment with Lower Levels of Physical Activity in Older Adults - Gispen, Fiona E. (2014)
OBJECTIVES: Identifying modifiable risk factors for decreased physical activity in older adults is important given the impact of physical activity on health. Whether hearing impairment, highly prevalent in older adults, is associated with activity levels is unclear. DESIGN: Cross-sectional analysis SETTING: 2005–2006 National Health and Nutritional Examination Survey PARTICIPANTS: 706 adults aged 70 years or greater who completed audiometric testing and whose physical activity was assessed subjectively with questionnaires and objectively with body-worn accelerometers MEASUREMENTS: Hearing impairment was defined by the speech-frequency (0.5 – 4 kilohertz (kHz) pure tone average in the better-hearing ear (normal <25 decibel (dB), mild 25 to <40dB, moderate or greater ≥40dB). Main outcome measures were self-reported leisure time physical activity and accelerometer-measured physical activity. Both were quantified using minutes of moderate-intensity physical activity and categorized into three levels: inactive, insufficiently active, and sufficiently active. Ordinal logistic regression analyses were conducted and adjusted for demographic and cardiovascular risk factors. RESULTS: Compared to those with normal hearing, individuals with moderate or greater hearing impairment had a greater odds of being in a lower category of physical activity as measured by self-report (OR=1.59, 95%CI: 1.11, 2.28) and accelerometry (OR=1.70, 95%CI: 0.99, 2.91). Mild hearing impairment was not associated with level of physical activity. CONCLUSION: Moderate or greater hearing impairment in older adults is associated with decreased levels of physical activity independent of demographic and cardiovascular risk factors. Future research is needed to investigate the basis of this association and whether hearing rehabilitative interventions could affect physical activity in older adults.